Structural barriers in accessing justice for victims of gender-based violence (Milan Law Review, 2024)
Reflections on structural causes of discrimination - such as, for example, those on epistemic injustice and stereotyping – are increasingly underlying the need for structured institutional intervention to address this problem. On this paper, the aim is to highlight the presence of different types of barriers that women encounter in accessing justice that lead to unequal treatment. To this end, the concept of "subordiscrimination" will be addressed, as it is related to the framework proposed by "anti-subordiscriminatory" law, which aims to eradicate those cultural and legal factors that are part of a system of asymmetrical power relations. Secondly, the concept of access to justice will be clarified, with an emphasis on equality from the perspective offered by the CEDAW. Finally, the paper will focus on the barriers that victims of gender-based violence face in accessing justice both at the socio-economic and cultural level as well as at the institutional level.
Keywords: Access to justice; CEDAW; Discrimination; Ideal Victim; Secondary Victimization